Characterization of cassava starch-based edible film enriched with lemongrass oil (Cymbopogon citratus) - RIANI RESIANINGRUM; WINDI ATMAKA; LIA UMI KHASANAH; KAWIJI KAWIJI; ROHULA UTAMI; DANAR PRASEPTIANGGA (Smujo International, 2016)
Abstract. Resianingrum R, Atmaka W, Khasanah LU, Kawiji, Utami R, Praseptiangga D. 2016. Characterization of cassava starch-based edible film enriched with lemongrass oil (Cymbopogon citratus). Nusantara Bioscience 8: 278-282.  Good packaging is necessary to prevent food spoilage before and after processing. The edible film maintains food quality and eco-friendly packaging. Cassava starch-based edible film is capable of being developed because of the approaching appearance of plastic packaging. The addition of essential oils can be used as an alternative to improve the antimicrobial properties of the edible film. Lemongrass oil consists of active compounds that shown antimicrobial activity. Therefore, the characteristics of cassava starch-based edible film incorporated with lemongrass oil were investigated. Concentration of lemongrass oils varied at 0%, 0.25%, 0.5%, 0.75% and 1%. The analyzed edible film characteristics include thickness, water vapor transmission rate, tensile strength, elongation, and antimicrobial activity. The results showed that the addition of lemongrass oil increased the thickness, tensile strength, and antimicrobial activity but decreased the elongation of edible films. The water vapor transmission rate of edible films was not affected by the addition of lemongrass oil.